1. Opuść nawiasy i zredukuj wyrazy podobne :
a) (3x- 2y +1 ) + 2(x + 3y - 2 )=
b) (-3)(-2a + 3b - 4) -4 (a+ ½b - 2) =
c) (4x² + 1,5x - 2)(-2) + ( -1,5)(x²-4x -1 ) =
d) 5(6ab - 4a - 2b +1) - 4,5(a- 2ab + b - 4 ) =

2. Opuść nawiasy i zredukuj wyrazy podobne :
a) 2a(b - 3a - 4) - 4b(a + 2b - 3,5) + (6a²+8a)=
b) (-3x)(2x + 4y + 1,8 ) + (2,5y - 3x - 1)(-4x)=
c) (-½)(x-4y)+ ( x - y + 2)(-3x) + 3x² =
d) (mn - 3m + 4n -2 )(-3m) + 2mn(-4m + 6)

3. Opuść nawiasy i zredukuj wyrazy podobne :
a) (5a - 2b)3b + (2a - 3b) a-b² =
b) 4x(x + y) + 3(x² - xy) - 5xy =
c) -x(4xy - 5a) + 3y(x² - 1) + x(xy - 5a ) =

2

Odpowiedzi

2010-03-05T21:31:01+01:00
1.a) (3x- 2y +1 ) + 2(x + 3y - 2 )=3x-2y+1+2x+6y-4=5x+4y-3
b) (-3)(-2a + 3b - 4) -4 (a+ ½b - 2) =6a-9b+12-4a-2b+8=2a-11b+20
c) (4x² + 1,5x - 2)(-2) + ( -1,5)(x²-4x -1 ) =
-8x^2-3x+4-1.5x^2+6x+1.5=9,5x^2+3x+5
d) 5(6ab - 4a - 2b +1) - 4,5(a- 2ab + b - 4 ) =
30ab-20a-10b+5-4,5a+9ab-4.5b+18=39ab-15,5a-14,5b+23
2.a) 2a(b - 3a - 4) - 4b(a + 2b - 3,5) + (6a²+8a)=
2ab-6a^2-8a-4ab-8b+14+6a^2+8a=-2ab-8b
b) (-3x)(2x + 4y + 1,8 ) + (2,5y - 3x - 1)(-4x)=-6x^2-12xy-5,4x-10xy+12x^2+4x =6x^2-22xy1,4x
c) (-½)(x-4y)+ ( x - y + 2)(-3x) + 3x² =-½x+2y-3x+3xy-6x+3x^2==-9½x+2y+3xy+3x^2
d) (mn - 3m + 4n -2 )(-3m) + 2mn(-4m + 6)=-3m^2n+9m^2-12mn+6m-8m^2n+12mn=-11m^2n+9m^2+6m
3.a) (5a - 2b)3b + (2a - 3b) a-b² =15ab-6b^2+2a^2-3ab-b^2=12ab-7b^2+2a^2
b) 4x(x + y) + 3(x² - xy) - 5xy =4x^2+4xy+3x^2-3xy-5xy=7x^2-4xy
c) -x(4xy - 5a) + 3y(x² - 1) + x(xy - 5a ) =-4x^2y+5ax+3x^2y-3y+x^2y-5ax=-3y






Najlepsza Odpowiedź!
2010-03-05T21:48:16+01:00
1.
a) (3x- 2y +1 ) + 2(x + 3y - 2 )=3x-2y+1+2x+6y-4=5x+4y-3
b) (-3)(-2a + 3b - 4) -4 (a+ ½b - 2) =6a-9b+12-4a-2b+8=2a-11b+20
c) (4x² + 1,5x - 2)(-2) + ( -1,5)(x²-4x -1 ) =-8x²-3x+4+(-1,5x²+6x+1,5)
=-8x²-3x+4-1,5x²+6x+1,5=-6,5x²+3x+5,5
d) 5(6ab - 4a - 2b +1) - 4,5(a- 2ab + b - 4 ) =30ab-20a-10b+5-(4,5a-9ab+4,5b-18)=30ab-20a-10b+5-4,5a+9ab-4,5b+18=39ab-24,5a-14,5b+23=-24,5a-14,5b=39ab+23
2.
a) 2a(b - 3a - 4) - 4b(a + 2b - 3,5) + (6a²+8a)=2ab-6a²-8a-4ab-8b²+14+6a²+8a=-2ab-8b²+14=-8b²-2ab+14
b) (-3x)(2x + 4y + 1,8 ) + (2,5y - 3x - 1)(-4x)=-6x²-12xy-5,4+(-10xy+12x²+4x)=-6x²-12xy-5,4-10xy+12x²+4x=6x²+4x-22xy-5,4
c) (-½)(x-4y)+ ( x - y + 2)(-3x) + 3x² =-½x+2y-3x²+3xy-6x+3x²=-6½x+2y+3xy
d) (mn - 3m + 4n -2 )(-3m) + 2mn(-4m + 6)=-3m²n+9m²-12mn+6m-8m²n+12mn=-5m²n+9m²+6m=9m²-5m²n+6m
3.
a) (5a - 2b)3b + (2a - 3b) a-b² =15ab-6b²+2a²-3ab-b²=2a²-7b²+12ab
b) 4x(x + y) + 3(x² - xy) - 5xy =4x²+4xy+3x²-3xy-5xy=7x²-4xy
c) -x(4xy - 5a) + 3y(x² - 1) + x(xy - 5a ) =-4x²y+5ax+3x²y-3y+x²y-5ax=-3y